The Standpoint of Intellectual Catholic Youth on Capitalism and Socialism in Lithuania between Two World Wars - Pruskus, Valdas (Problemos, 2002)
Intellectual Catholic youth (A. Maceina, P. Jakas, P. Dielininkaitis and others) observed and identiñed the real consequences of the results of the development of capitalistic system at that time and its influence upon a human spirit and the possibilities of self-expression of an individual. They recognized that the key law of capitalism - to get and accumulate profits - provokes a social stress between employers (owners) and employees. It was thought that such stress may be overcome in the only way: employers and employees must willingly and consciously restrict their egoism and look for a cooperation (partnership), but not for a confrontation. A possibility of a cooperation is shown to be possible by a circumstance that a “capitalistic spirit” is hidden in each individual and it induces the individual to act and pursue benefit, to care of himself. It is important to form the conditions to everybody to realize this aim in practical activities, considering an individual not a mean to pursue the stated object, but a close person, who needs not only a compassion, but a concrete assistance as well. According to their standpoint, an individual shall provide a social support to him(her)self by honest and responsible performance of the assumed duties, being worthy of the corresponding renumeration for it. He (she) shall be entitled to receive an extra pay in a case of an acquisition of shares of an enterprise, when conscious and voluntary assuming of the right of risk takes place. However, acquisition and selling of shares shall not be an obligation, but only a free and voluntary self-determination. On the other hand, an individual must feel a real support of the state as well, and its task of paramount importance shall be a formation of the conditions for everybody and each member of the society to pursue their objects, taking into account the highest value - a human and his dignity, which cannot be sacriñced to the seeming omnipotence of the faceless machine building. Taking into consideration that the object of economical activities is a satisfaction of needs of an individual and the society, their results shall be evaluated not only in the economical scale (benefit), but in the ethical (a non-contradiction to aims of self-expression of an individual) scale. The intellectual Catholic youth singled out socialism as a theoretical model and the practice of socialism as its implementation in the realty. In their critical evaluation of the measures of restoration of justice, suggested by adepts of socialism, especially a compulsory socialization of the means of production, they disclosed social and economical inefficiency of mechanical transformations, its contradiction to the nature and aspirations of a human. Simultaneously they recognized an importance of social transformations in a restoration of social justice but considered a spiritual stimulus to be of the key importance in a successful realization of such transformatíons. Namely the absence of it causes a soullessness and hostility, which in social plane are mostly expressed in relations of employers and employees. The young intellectual Catholics tried to single out the factors which united, but not separated them. They demystificated the working class, considered to be a generous, noble fighter for a welfare of the whole mankind, showing that the objects of workers are the same egoistic as the ones of bourgeoisie: to “survive” in this reality, to ensure a satiated and safe life as the one of employers, already consolidated themselves in the reality. So, the youth destroyed the myth about the working class as the only noble fighter for a welfare of the whole mankind, its exclusive mission which was stressed by local adepts of socialism. The transformations performed by the real socialism in the Soviet Union, were unacceptable to intellectual Catholic youth, because they were performed under compulsion, ignoring the grade of spiritual and social maturity of the society. On the other hand, the youth did not reject a possibility of development of socialism as a social system, which would reduce a stress between various strata of the society, having their own interests, and help to realize a justice more completely, in a course of time, after the corresponding preparation of the society. However, it would require spiritual efforts of an individual and the society to overcome a human and social egoism, to cultivate a good will, a feeling of Christian responsibility and solidarity and in this way to prepare themselves for social transformations. Although intellectual Catholic youth of Lithuania linked socialism with a certain level of a spiritual maturity of humans, on which socially responsible transformations will be possible, they did not consider socialism to be an inevitable and objective regularity of evolution of the society. Aspiration to socialism as the ideal of a better and more truthful society depends on a human; its realization more depends on the consciousness and efforts in spiritual and cultural improvement of an individual than the will of the state, the goveming party. Nobody knows and can exactly say, how long it will continue, but it is a matter of a human, not of history. So, the youth virtually negated the Statement on socialism as an inevitable and lawful result of evolution of the society and in this way opposed to the efforts of local communists and the left intelligentsia to present such role of it to the society of that time. Stressing the importance of conscious efforts of an individual in striving for a better life, they belittled the pretensions of local communists to be leaders of the Working people to the bright future, shielding themselves with the veil of fighters for social equality and social justice, and in this way to be entitled to become the masters and uncontrolled managers of that future. On the other hand, stressing a necessity of a respect to a personality of an individual, his/her spiritual aspirations in a performance of social transformations, the young intellectual Catholics encouraged to take an attentive look at the social experiment performed in the neighbouring state - Soviet Russia. They encouraged to evaluate more critically the prophecies of local adepts of socialism as well. In this way they warned the Lithuanian people on the possible consequenccs of such social experiment, realized under compulsion.